Cytotoxic Flavonoids from Lannea egregia Engl. & K. Krause - Oluwatosin T. Ayodele; Olaoluwa O. Olaoluwa; Saheed O. Benson; Olapeju O. Aiyelaagbe; Lutfun Nahar; Amos A. Fatokun; Satyajit D. Sarker (Tabriz University of Medical Sciences, 2024)
Background: Lannea egregia Engl. & K. Krause (family: Anacardiaceae) is a well-known medicinal plant in Nigeria whose various parts have been shown to elicit several biological activities. This study specifically explored the leaf of L. egregia for potential cytotoxic compounds. Methods: n-Hexane, dichloromethane and methanolic extracts of the leaf were prepared using the Soxhlet apparatus and concentrated using the rotary evaporator. Compounds were isolated by reversed-phase preparative high-performance liquid chromatography, and the structures were determined by spectroscopic means. The methanolic extract and the isolated compounds were screened for cytotoxicity against HeLa and MCF-7 cancer cell lines, using the MTT assay. Results: Three flavonoids, myricetin (1), myricetin 3-O-α-L-rhamnoside (2) and quercetin 3-O-α-L-rhamnoside (3), were isolated from the methanolic extract of the leaf of L. egregia. The methanolic extract and compound 3 showed the most potent inhibition profiles against the cells, with IC50 values (Mean ± SEM) of 45.3 ± 1.5 µg/mL and 57.5 ± 0.4 µg/mL for the methanolic extract, and 36.5 ± 2.0 µM and 57.9 ± 10.1 µM for compound 3, against HeLa and MCF-7 cells, respectively. Conclusion: Conclusion: This work shows that L. egregia leaf is moderately cytotoxic, and rich in flavonoids, and the cytotoxicity of the extract is, at least partially, due to the presence of cytotoxic flavonoids. This is the first report on characterized isolated compounds from the leaf of L. egregia and the occurrence of flavonols in the leaf.